Apontamentos sobre Cooperação entre Brasil - Angola no que se Refere à Segurança Alimentar e Nutricional - Rocha, Andréa Pires [UNESP]; Dos Santos, José Francisco (My University, 2015)
This article discusses the issue of combating hunger in Brazil and Angola, addressing aspects of cooperation between the two countries as regards the assurance of the Human Right to Adequate Food and Food and Nutrition Security. We conducted desk research reports from international organizations and agencies as well as in official agreements present in the Foreign Ministry website. The discussion is divided into four parts, which involve the historical review of the relationship Brazil - Angola in the political and economic sense; phenomenon of food insecurity in the two countries; the direct link between the choice of a model of agriculture and the guarantee of SAN; presentation of specific initiatives for cooperation between Brazil and Angola. Finally denounced the problem of persistence of the phenomenon of hunger and the urgent need for understanding of the right nutrition as a human right.
Notes on cooperation between Brazil - Angola regarding food security and nutrition
Keywords: Angola; Brazil; Food and Nutrition Security; Human Right to Adequate Food; International cooperation